Gentrification and Resistance Researching Displacement Processes and Adaption Strategies (Springer Fachmedien Wiesbaden : VS, 2018)
Gentrification is arguably the most dynamic area of conflict in current urban development policy - it is the process by which poorer populations are displaced by more affluent groups. Although gentrification is well-documented, German and international research largely focuses on improvements in the built environment and social composition of neighbourhoods. The consequences for those who are displaced often remain overlooked. Where do they move? What does it mean to be forced to leave a familiar residential area? What kinds of resistance strategies are developed? How does anti-gentrification work? With a focus on Berlin - the German "capital of gentrification" - the chapters in this volume use innovative methods to explore these pressing questions. Contents Gentrification and Displacement Gentrification in Subsidized Rental Housing Hotspots of Gentrification New Forms of Displacement and Protest The State-Made Rental Gap Trailer Living as Displacement Phenomenon Residential Biographies as an Instrument of Sociospatial Displacement Analysis Target Groups Researchers and students in the fields of sociology, urban studies, geography, and urban planning Practitioners in the fields of urban planning, housing policies, and neighbourhood development The Editor Ilse Helbrecht is director of the Georg-Simmel-Centre for Metropolitan Development and full professor of social and cultural geography at Humboldt-Universität Berlin. She works on gentrification, housing, and urban governance.